Occupational participation and social inclusion of the LGBTIQ+ community in the Magallanes region and the Chilean Antarctic Territory - Palma Candia, Oskarina Carmen; Rojas Villegas, Katherine; Soliz Soliz, Carla; Venegas Navarrete, Lucha (My University, 2022)
Introduction: People of sexual diversity have been violated in their human rights and marginalized from participating in some spaces, and occupations as a result of prejudices and social constructions that have been imposed as the predominant culture throughout history. Objective: To know the perception of people from the LGBTIQ+ community, about their social inclusion and occupational participation in the different spaces of daily life in the Magallanes and Chilean Antarctica region. Method: Semi-structured interviews were applied to LGBTIQ+ people between 20 and 40 years old, the stories were interpreted through content analysis, using qualitative methodology with a descriptive approach. Results: Different opinions are obtained about the occupational participation of LGBTIQ+ people, pointing out some positive experiences of acceptance, however, experiences of discrimination and violence predominate, as well as situations of injustice or occupational deprivation as a result of prejudices and beliefs, both social and personal (occupational awareness), According to the reports, needs and proposals are collected to achieve occupational participation and full inclusion. Conclusion: The occupational participation and social inclusion of the LGBTIQ+ community are affected by discrimination, prejudice, and beliefs of people in the Magallanes region, showing that progress is still required, and generate spaces for training and re-education related to sexual and gender diversity, deconstructing the prejudices and beliefs that persist in the region.
Keywords: gender diversity; social participation; occupational therapy; social justice; activities of daily living